Adjusting The Concept Of Particularly Sensitive Sea Area Into Lombok Strait Configuration (International Forum of Researchers and Lecturers, 2024)
This article investigates the adverse impacts of unintentional or operational ship discharges on marine ecosystems and elucidates the significance of Particularly Sensitive Sea Areas (PSSA) as an approach to safeguard the marine environment from international shipping activities. Focusing on IMO resolutions and the United Nations Convention on the Law of the Sea (UNCLOS) framework, the article analyzes the PSSA concept, underscores its role in pollution prevention, and explores inherent limitations. Specifically, it delves into the legal status of PSSA, the binding nature of IMO resolutions, and implementation challenges. Through in-depth analysis, the author concludes the necessity for revising PSSA resolutions to enhance legal clarity and effectiveness in marine environmental protection.